Precise Tide-independent Bathymetric Survey and Application to the Inshore Monitoring of Seabed Evolution - Zhao, Jianhu; Zhang, Hongmei; Wang, Shengping (The International Hydrographic Review, 2008)
Due to the influences of tidal water level, vessel attitude and wave motion, the traditional bathymetric method of reducing depths by the tidal level makes it difficult to meet precise engineering requirements in the vertical direction. Therefore a precise method, termed a tide-independent bathymetric survey, is presented in this paper. In this method, the quality of the sounding and positioning solution, the influences of time offset and vessel attitude as well as height transformation are considered by taking a series of measurements. The tide-independent method has been used for inshore monitoring of the seabed sediments. The statistical parameters acquired by comparing the traditional method with the tide-independent method used in the monitoring show that the latter is accurate and credible.